NEEDS ANALYSIS OF ENGLISH LEARNING FOR MEDICAL STUDENTS AT PRIVATE UNIVERSITIES IN PEKANBARU CITY - Indrapuri, R. Sri Ayu; Mahdum, Mahdum; Azhar, Fadly; Erni, Erni (Jurnal Warta Dharmawangsa, 2025)
English learning is an important asset for medical faculty students to face various future challenges in the health profession. Of course, the role of lecturers is very important in helping students acquire adequate English language skills. For English lecturers who teach medical students (English for Specific Purposes), lecturers are asked to develop syllabus and teaching materials based on student needs. Lecturers need to effectively meet the professional needs of students in the real world. However, the problem, especially in Pekanbaru city there are still many English lecturers who teach in the health sector who have difficulty designing teaching materials that are appropriate to the student's field of knowledge. The purpose of this study is to analyze the English learning needs of medical students. The method used in this study is a qualitative approach through a survey. The population in this study were students of the medical Faculty, especially private Universities in Pekanbaru city. The research implementation period starts from June 2024. The results of this study are expected to be useful for lecturers who teach medical Faculty students to improve students' English skills that are appropriate for the Health sector then be able to continue research on the development of learning modules.